Análise da estrutura física do Arquivo Central da UFPA a partir das normas e recomendações do CONARQ - GOMES, Danilo Lucas da Conceição (2022)
Analysis of the physical structure of the Central Archive of the UFPA, taking with reference to the standards and recommendations of buildings files CONARQ 2000, written by the museologist Ingrid Beck. For the application of the work were used the interviews and a checklist in place, whose items reviewed were the ceiling, walls, doors/windows, furniture, hvac, security, and control of water. The results indicate that the central archive of the UFPA has obtained a positive perspective, with some deviations, in particular in the small work space and and air-conditioning. The work highlights the importance of an infrastructure, care in the physical space of the acquis, in addition to serving as a basis for further research and analysis on the physical spaces of files.